Design and fabrication of home automation. (October 2019) - Vignesh, T; Selvakumar, D; Prasath, C; Manikandan, N; Sri Viswanath, R
Abstract: The objective of this project is to control all electronic device in the house, remotely and to automate some parts of the house like pipes, garage using Arduino or raspberry pi. The raspberry pi is a microprocessor which can be used for multiple purposes like getting input signal, based on the signal the output is calculated and sent to the actuators. Here we use raspberry pi board, few dc motors (this motor works on dc using permanent magnet), LED lights and a model of 3d model of the house. The prototype model build using 3d printer and electrical bulb, doors, fan and washing machine are demonstrated. This project will be a real-world model which will have the ability to perform task of operating devices, remotely. This project will help the people to keep an eye on their house when they are not home and help to on or off some of the appliances when they are away from home.